BIOCHEMICAL AND GENETIC ASPECTS OF THE CHRONIC OBSTRUCTIVE PULMONARY DISEASE AND ARTERIAL HYPERTENSION COMBINATION - O. S. Polunina; I. V. Sevostyanova; A. Kh. Akhmineeva; L. P. Voronina (Кубанский научный медицинский вестник, 2014)
The content of endothelium-1 and C-type natriuretic peptide in the blood plasma in correlation with the gene polymorphism of endothelial nitric oxide synthase was studied in 35 patients with chronic obstructive pulmonary disease (COPD), 35 patients with arterial hypertension (AH) and in 40 patients with the diseases combination (COPD+AH). VNTR-polymorphism causes the hyperproduction of endothelium-1 and C-type natriuretic peptide in patients with a single disease and with the COPD+AH combination. The arterial hypertension conjunction in patients with COPD doesn't influence significantly the microvascular endothelium status, but the endothelial dysfunction presence in patients with COPD may be a precondition for the arterial hypertension progression.